Lean Manufacturing Implementation in Developing Countries:Evidence from Jordanian Industrial Companies - AlMadi , Faisal; Mansour, Ala a Zuhair; Alhatabat, Zaidoon; Ershaid, Diala; Irshoud , Jafar (South Asian Journal of Social Sciences and Humanities, 2024)
In today's fiercely competitive landscape, industries are increasingly embracing lean manufacturing strategies for survival. However, the adoption of lean principles in Jordanian manufacturing sectors remains relatively new. This study aims to evaluate the current state of lean adoption in Jordanian industries, focusing on its techniques, motivations, and challenges. Employing a quantitative methodology, surveys targeted Production, Operation, and Quality Managers in Jordanian organizations. Out of 300 distributed questionnaires, 176 valid responses were received, representing a response rate of 58.7%. The findings indicate a relatively low adoption of lean practices in Jordanian industries, though firms that have implemented lean report significant benefits, particularly in quality enhancement and cost reduction. Key challenges include inadequate training, a scarcity of experts, and complexities in small batch production. While the study's sample size is limited, caution is warranted in interpreting the results. Further empirical research is needed to quantify the performance benefits of lean adoption. This study sheds light on lean adoption in Jordanian manufacturing, informing knowledge development and guiding future efforts to promote lean practices in the industrial landscape.
Keywords: Lean Implementation; Developing Country; , Industrial Companies; Jordan